Implementation Of Focus Explore Reflect Apply (FERA) Learning Model Assisted Crocodile Physics In Improving Students’ Critical Thinking Skills - Nurhalimah, Siti; Rizal, Rahmat (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This study aimed to determine the effect of the Focus Explore Reflect Apply (FERA) learning model assisted by crocodile physics media on students’ critical thinking skills on sound waves material and to determine the increase in critical thinking skills in students on sound waves material in class XI IPA SMA Negeri 1 Cihaurbeuti. The research method used was quasi-experimental with a research design non-equivalent control group design. The population of this study was all XI IPA classes, as many as seven classes, using purposive sampling techniques, selected as many as two classes, namely XI IPA 3 as the experimental class and XI IPA 2 as the control class. The essay test was conducted before and after treatment with nine questions on sound wave material to measure critical thinking skills. The essay question includes five indicators of critical thinking skills. The data analysis techniques used are prerequisite tests (normality test, homogeneity test) and hypothesis testing (t-test). The results of hypothesis testing using the t-test showed that after the application of the Focus Explore Reflect Apply (FERA) learning model assisted by crocodile physics media,  (3.74> 1.6), so  is rejected and  is accepted. It means that applying the Focus Explore Reflect Apply (FERA) learning model assisted by crocodile physics media is proven to affect critical thinking skills in sound wave material. Improved critical thinking skills can be seen from the results of the N-Gain, where both classes are in the medium category, but the experimental class scores are more significant than the control class.This study aimed to determine the effect of the Focus Explore Reflect Apply (FERA) learning model assisted by crocodile physics media on students’ critical thinking skills on sound waves material and to determine the increase in critical thinking skills in students on sound waves material in class XI IPA SMA Negeri 1 Cihaurbeuti. The research method used was quasi-experimental with a research design non-equivalent control group design. The population of this study was all XI IPA classes, as many as seven classes, using purposive sampling techniques, selected as many as two classes, namely XI IPA 3 as the experimental class and XI IPA 2 as the control class. The essay test was conducted before and after treatment with nine questions on sound wave material to measure critical thinking skills. The essay question includes five indicators of critical thinking skills. The data analysis techniques used are prerequisite tests (normality test, homogeneity test) and hypothesis testing (t-test). The results of hypothesis testing using the t-test showed that after the application of the Focus Explore Reflect Apply (FERA) learning model assisted by crocodile physics media,  (3.74> 1.6), so  is rejected and  is accepted. It means that applying the Focus Explore Reflect Apply (FERA) learning model assisted by crocodile physics media is proven to affect critical thinking skills in sound wave material. Improved critical thinking skills can be seen from the results of the N-Gain, where both classes are in the medium category, but the experimental class scores are more significant than the control class.